Earthquake impact image contrast enhancement - Suzelawati Zenian (Faculty of Science and Natural Resources, 2020)
Contrast enhancement plays an important role in image processing. It aims to improve the visibility of objects by enhancing the overall visual representation of the images. In this paper, the contrast of earthquake impact image in Ranau, Sabah is enhanced by using classical technique namely Image Size Dependent Normalization (ISDN). Moreover, a comparison is carried out between ISDN and another classical technique known as Histogram Equalization (HE). The accuracy of both methods is measured by using universal image quality index (UIQI) metric.